(untitled) (Research, Society and Development, 2022)
The objective of the present study is to describe what scientific publications say about the health problems caused by the SARS-CoV-2 virus on the pregnant woman and the fetus during the gestational period. Which presents an integrative literature review methodology, where the construction of the study was based on the question “What is the impact of the SARS-CoV-2 virus on the pregnant woman and the fetus during the gestational period?”. The searches were carried out in the Virtual Health Library, in the Medline, Lilacs and Bdenf databases using the descriptors “Pregnant women”, “SARS-CoV-2”, “Complications”. The bibliographic survey was carried out on articles from the years 2020 to 2022. After the inclusion and exclusion criteria, 13 articles remained that were read and evaluated in full to compose this study. An important point was discussed and observed, which is the clinical approach by performing prenatal care in patients affected by COVID-19. The most common gestational manifestations were premature rupture of membrane, preeclampsia, fetal distress and preterm delivery. Regarding pregnant women, most, when infected, were asymptomatic for the disease. In this way, it is concluded that more studies are needed on this topic in order to clarify the impacts of the virus on the pregnant woman and the fetus for a better understanding of the subject, as well as the importance of carrying out prenatal care.